THE RELATIONSHIP OF KNOWLEDGE ABOUT HAZARD PREGNANCY ON PREGNANT MOTHER IN THE THIRD TRIMESTER AT NORTH PUSKESMAS BOGOR: HUBUNGAN PENGETAHUAN TENTANG TANDA BAHAYA KEHAMILAN DENGAN PERILAKU PERAWATAN KEHAMILAN PADA IBU HAMIL TRIMESTER III DI PUSKESMAS BOGOR UTARA - Hani Siti Hanifatun Fajria; Nurbaeti Nurbaeti Amilia (Jurnal Ilmiah Wijaya, 2019)
Knowledge of Obstetric Danger Signs and Pregnancy Caring Behaviors among Third Semester Pregnant Women. Obstetric complications have been known as one of the causes of high maternal mortality rate. Women knowledge in recognizing danger signs can be one of the determinations of pregnancy caring behaviors in preventing further complications. This study aimed to determine the relationship between knowledge of obstetric danger signs and pregnancy care behavior among third trimester pregnant women. This study applied a descriptive design with cross sectional approach. Purposive sampling used as sampling technique. Samples of this study were 83 third trimester pregnant women in health care center. This study showed that there was no statistically significant relationship between knowledge of obstetric danger signs and pregnancy care behaviors among third trimester pregnant women (p = 0,678; α = 0,05). this study recommends that health care professional should motivate pregnant women to take care of their pregnancy.